Strategic Proposals for Educational Management of Dual Education in Secondary Schools under the Secondary Educational Service Area Office 22 and 23 - Nardkosa, Bodin; Pawabutra, Chaiya; Suwannatri, Watana (NEU ACADEMIC AND RESEARCH JOURNAL, 2021)
The purposes of this research were to examine components, indicators and needs for educational management in dual education in secondary schools under the Secondary Educational Service Area Office (SESAO) 22 and 23, and to develop and validate the proposed strategies for educational management of dual education in secondary schools under the SESAO 22 and 23 in terms of appropriateness, feasibility, congruence, usefulness, and operational guidelines to success. The policy research was conducted in three phases: Phase I- Examining fundamental information through document inquiry, interviews with experts in the field of education, a survey, and multi-case studies; Phase II- Drafting strategic proposals through an expert assessment; and Phase III- Conducting Public hearing with stakeholders. The research instruments consisted of a set of questionnaires, in-depth interview forms, strategy assessment forms, and questionnaires for public hearings. Statistics for data collection were percentage, mean, and standard deviation. The findings were as follows: 1. The five components of educational management of dual education in secondary schools under the SESAO 22 and 23 consisted of five aspects with 67 indicators: 1) Administrative management, 2) Teaching and learning management, 3) Curriculum development, 4) Personnel development, and 5) Networking and cooperation. The results of needs assessment showed that overall, the priority needs index (PIN Modified) of all aspects was 0.27. The personnel development reached the highest level of needs. 2. The strategic proposals for educational management of dual education in secondary schools under the SESAO 22 and 23 consisted of five components: 1) visions, 2) missions, 3) goals, 4) strategic issues, 5) strategies/indicators, and 6) operational guidelines to success. The five strategic issues, consisted of 12 strategies, and 35 indicators/operational guidelines to success, achieved the highest level in terms of appropriateness, feasibility, congruence, usefulness, and operational guidelines to success. The strategy on administrative management reached the highest mean scores.